PENGARUH FAKTOR INTERNAL PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN PERUSAHAAN FARMASI TERDAFTAR DI BURSA EFFEK INDONESIA PERIODE 2008-2014 - Siagian, Arifin; Doni Graha Saputra (Pasca Sarjana Universitas Satya Negara Indonesia, 2017)
This study aims to examine and analyze the effect of internal determinant dividend payout ratio pharmaceutical company, annual data observation period 2008 until 2014. Type studies quantitative research. Population of the entire pharmaceutical company amounted of 10 companies, criteria sampled pharmaceutical company that consistently pay cash dividends, found 6 companies listed in Indonesia Stock Exchange with non probability sampling technique is purposive sampling. Analysis data with panel data regression fixed effect which has value R-square larger. The results showed that current ratio, return on assets, debt to equity ratio, earnings growth, return on equity, earnings per share and market to book value simultaneously are having significant influence to the dividend payout ratio. Partially return on assets and market to book value has a positive significant effect on the dividend payout ratio, while of current ratio, debt to equity ratio and return on equity has a significant negative effect. Earnings growth and earnings per share are not having significant influence on the dividend payout ratio. Suggested adding variables external factors, using a sample of companies for more.